An Assessment of the Environmentally Sustainable Hotel Operation: The Case of Centara Hotels & Resorts, Thailand - Baxter, Glenn; Srisaeng, Panarat (วารสารเพื่อการพัฒนาการท่องเที่ยวสู่ความยั่งยืน, 2021)
Utilizing an in-depth qualitative longitudinal research approach, this study has empirically examined the environmentally sustainable hotel operations of Centara Hotels & Resorts. The study period was from 2015 to 2020. The qualitative data was analyzed by document analysis. The company’s annual Scope 1 and Scope 2 greenhouse gas emissions increased over the study period in line with its operational requirements. The case study revealed that energy consumption and wastes had displayed a downward trend over the study period, which had a favorable environmental impact. The company’s water consumption remained relatively constant throughout the study period. The company has implemented a wide range of energy and water saving measures. Wherever possible wastes are re-used, recycled, or composted and only wastes not suitable for re-use, recycling or composting are disposed to landfill. Centara Hotels & Resorts has also implemented a carbon sequestration program that is assisting the company to reduce its carbon footprint.